2012
DOI: 10.1136/emermed-2012-201610
|View full text |Cite
|
Sign up to set email alerts
|

Rescuer fatigue under the 2010 ERC guidelines, and its effect on cardiopulmonary resuscitation (CPR) performance

Abstract: Fatigue affects chest compression delivery within the second minute of CPR under the 2010 ERC guidelines, and is poorly judged by rescuers. Rescuers should, therefore, be encouraged to interchange after 2 min of CPR delivery. Team leaders should be advised to not rely on rescuers to self-report fatigue, and should, instead, monitor for its effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 18 publications
4
72
2
6
Order By: Relevance
“…Vertical bars indicate 0.95 confidence intervals during external cardiac compression [10], which could also be observed in this study. The average chest compression depth gradually decreased during the task and in the 2 nd minute the depth was already insufficient (< 40 mm).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Vertical bars indicate 0.95 confidence intervals during external cardiac compression [10], which could also be observed in this study. The average chest compression depth gradually decreased during the task and in the 2 nd minute the depth was already insufficient (< 40 mm).…”
Section: Discussionsupporting
confidence: 58%
“…It has been assumed that it is possible to prolong the period of time between rescuer change even up to 10 minutes. This suggestion seems to be reasonable as none of the participants of this study mentioned fatigue, and in other sources, fatigue was the most frequently noted factor demanding rescuer change during external cardiac massage [10,17,19,20,21]. Other complaints (wrist pain, knee pain, lumbosacralis pain) indicated by the CCC-CPR rescuers were similar to those found in other sources but they came out relatively late during observation and were not a reason to stop resuscitation [22].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, some studies demonstrate that the quality of CPR performance during SCA is poor, even when CPR is conducted by medical staff [4][5][6][7]. Due to the fact that CC must be performed as continuously as possible and maintained over time, fatigue may be also a critical quality factor in CC [8][9][10]. European Resuscitation Council (ERC) guidelines have acknowledged this evidence and recommend a switch of rescuers every 2 min [1].…”
Section: Introductionmentioning
confidence: 99%
“…(6) Several manikin studies have revealed that BLS quality drops significantly during the first two minutes, especially the depth of compression, even when verbal feedback was provided in case of decreased compression depth. (7)(8)(9)(10)(11)(12)(13) These studies offer sophisticated insight into the process of BLS in terms of physical capabilities of providers. However, we still do not have the answers to the following questions: Do subjective parameters positively correlate with objective ones?…”
Section: Discussionmentioning
confidence: 99%